An Approach to Compress EEG Signal Using Wavelet Based MSPCA Algorithm: Efficient compression of EEG signals using Wavelet Based MSPCA Algorithm (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“The Main objective of this paper work is based on implementing a technique to compress the EEG signal using multiscale PCA algorithm with wavelet.” This paper is focuses on the technique providing expansive coverage of algorithm and tools from the field of digital signal processing. This concept motivated to develop a method which compress the EEG signal without degradation to accuracy and without loss of data.” The motivation for this research is the large amount of low amplitude data involved in collecting EEG information which requires storage space and high bandwidth for transmission.”